Removal of Methylene Blue from Water Using Magnetic GTL-Derived Biosolids: Study of Adsorption Isotherms and Kinetic Models - Shifa Zuhara (14150862) (2023)
Global waste production is significantly rising with the increase in population. Efforts are being made to utilize waste in meaningful ways and increase its economic value. This research makes one such effort by utilizing gas-to-liquid (GTL)-derived biosolids, a significant waste produced from the wastewater treatment process. To understand the surface properties, the biosolid waste (BS) that is activated directly using potassium carbonate, labelled as KBS, has been characterized using scanning electron microscopy and energy dispersive X-ray spectroscopy (SEM-EDS), X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction (XRD), and Brunauer–Emmett–Teller (BET). The characterization shows that the surface area of BS increased from 0.010 to 156 m2/g upon activation. The EDS and XPS results show an increase in the metal content after activation (especially iron); additionally, XRD revealed the presence of magnetite and potassium iron oxide upon activation. Furthermore, the magnetic field was recorded to be 0.1 mT using a tesla meter. The magnetic properties present in the activated carbon show potential for pollutant removal. Adsorption studies of methylene blue using KBS show a maximum adsorption capacity of 59.27 mg/g; the adsorption process is rapid and reaches equilibrium after 9 h. Modelling using seven different isotherm and kinetic models reveals the best fit for the Langmuir-Freundlich and Diffusion-chemisorptionmodels, respectively. Additional thermodynamic calculations conclude the adsorption system to be exothermic, spontaneous, and favoring physisorption. Other Information Published in: Molecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/molecules28031511